Busca de extratos e compostos ativos com potencial herbicida e inseticida nas espécies Davilla elliptica St. Hill e Ocotea pulchella Nees & Mart - Candido, Lafayette Pereira (Universidade Federal de São Carlos, 2016)
Brazil by presenting incomparable biodiversity, distributed in mosaic wonderfully distinct biomes becomes a promising the field of study in seeks of new phytochemicals extracted from native plants with biological activity on weeds and insects of medical importance. Species of Lauraceae and Dilleniaceae family have an immense potential in the production of secondary compounds with herbicide and insecticide properties. Thus, this study objective was to clarify the following questions: leaf extracts the stem and root Ocotea pulchella and Davilla elliptica could interfere with the growth and development of Triticum aestivum, Euphorbia heterophylla and Panicum maximum and thus make a new alternative for the control of weeds? Amongst the donor species and crude extracts which more promising to start a bioprospecting, allowing isolate and identify the present compounds? The extracts show insecticidal activity against eggs and larvae of Aedes aegypti? Coleoptile bioassays were performed using hexane extracts, dichloromethanic, acetoetilicos, methanolic and aqueous leaf, stem and root of O. pulchella and D. elliptica 0.2, 0.5 and 0.8 mg.mL-1. Most active extracts have been evaluated on the germination and early seedling growth of E. heterophylla and P.maximum using doses of 0.25, 0.5, 1 and 2 mg.mL-1. The larvicidal activity was evaluated at concentrations of 0.25, 0.5, 1, 2 and 3 mg.mL-1 and ovicidal effect with the LC50 and LC90 lethal concentrations estimated in test A. aegypti larvae. The leaf extracts O. pulchella inhibit coleoptile growth of wheat and seed germination and seedling growth of weeds and standard species. In general, the ethyl acetate extract O. pulchella showed higher phytotoxic activity. Eleven compounds were isolated and characterized. Compounds 1, 2, 4 and 6 have not been identified before in O. pulchella and Ocoteol was first described in the literature. The compounds 5, 10 and 11 were most active with superior inhibition values of 90% in the standard species. P. maximum has been the target species most affected by O. pulchella and D.elliptica leaf extracts in all evaluated parameters. The reduction in root growth of wild poinsettia seedlings can be related to the decrease in the elongation of metaxylem cells submitted at the ethyl acetate extract (O. pulchella) and methanol (D.elliptica). The extracts from root hexane and dichloromethane O. pulchella at a concentration 3 mg.mL-1 have produced bigger effect larvicide. Lower values of CL50 and CL90 were estimated for larvae subjected to the root extract from O. pulchella dichloromethane. Hatching rate, TME and VME have been affected by DCM and hexane root extracts from O. pulchella. Specie O. pulchella showed higher potential herbicide on the germination and the growth pattern and weed species and insecticide on larvae and eggs of A. aegypti.
Keywords: Davilla elliptica; Aedes aegypti; Cerrado; Aleloquimicos; Ocotea pulchella; Phytotoxins; Phytotoxins; Allelochemicals; Control; Herbicide; Insecticide; CIENCIAS BIOLOGICAS::ECOLOGIA